The Kashmir Dispute, 1947-2012 - Noorani, A. G. (Karachi Oxford University Press, 2014)
'The Kashmir Dispute, 1947-2012' traces the complex history of this long-standing issue, and the political discontent and dissent surrounding it - relating especially to the question of the accession of the state of Jammu and Kashmir to the Union of India.
Include Appendix and Index.
Keywords: India--Jammu and Kashmir -- Politics and government